Inhibition of copper/quinoprotein amine oxidases from Aspergillus niger by benzophenanthridine alkaloids - Luhová, L; Frébort, I; Ulrichová, J; Adachi, O; Simánek, V; Pec, P (Journal of enzyme inhibition, 1995)
Inhibition of copper/quinoprotein amine oxidases (EC 1.4.3.6), AO-I (dimer 2 x 75 kDa) and AO-II (monomer 80 kDa), from the fungus Aspergillus niger by benzophenanthridine alkaloids sanguinarine, chelerythrine, and fagaronine were studied. For both amine oxidases the alkaloids showed reversible noncompetitive inhibition of n-hexylamine oxidation with Ki 0.6, 0.9 and 2.8 mM for sanguinarine, chelerythrine, and fagaronine, respectively. The values of the inhibition constants corresponded to pKR+ values for the iminium ion/pseudobase equilibrium of the alkaloids. Since thio-compounds protected the enzymes against this inhibition, the inhibition effect was ascribed to the interaction with a sulfhydryl group essential for the enzymatic activity.
Keywords: Phenanthridines; benzofenantridiny; vztah mezi dávkou a účinkem léčiva; Benzophenanthridines; histaminasa; alkaloidy; Amine Oxidase (Copper-Containing); Isoquinolines; isochinoliny; Enzyme Inhibitors; inhibitory enzymů; Alkaloids; Dose-Response Relationship, Drug; fenantridiny; Aspergillus niger